Understanding father involvement in the education of learners with intellectual disabilities in a special school in Kenya: a case study - Karisa, Amani (Department of Health and Rehabilitation Sciences, 2020)
There are known benefits of father involvement in a child's life, such as positively affecting the child's life prospects, academic achievement, physical and emotional health as well as linguistic, literary and cognitive development. In African settings, fathers are traditionally the heads of families and the main decision makers in matters like the education of their children. However, a limited body of scientific knowledge exists on fathers' roles and involvement in the education of their disabled children in the African context. To address this knowledge gap, a qualitative case study to understand the nature of father involvement in the education of learners with intellectual disabilities in a special school in Kenya was conducted. The research question was: what is the nature of father involvement in the education of disabled learners at Sir Ali Special School, Kenya? The study was guided by theoretical perspectives from disability studies in education, masculinity and postcolonial theory. The field of disability studies in education focuses on the application of the social model of disability in an education context. The theories of masculinity look at the social construction of the male identity, and the postcolonial theory explores the colonial legacy of the study context. The data were collected from eight fathers, six mothers, nine teachers and six disabled learners using individual interviews, key informant interviews, draw-and-tell interviews, focus group discussions, document review and field notes. The data were analysed thematically. Three themes emerged from the data analysis: influence of cultural norms and values on father involvement, fathers' concerns in educating disabled children, and impact of understanding disability on father involvement. It was established that the intersection between patriarchy and masculinity affects normative gender roles that influence father involvement in the education of disabled children in a dynamic context. It was also evident that the cost of disability is greater than that of nondisability and this influences how fathers are involved in the education of their disabled children. Additionally, fathers wanted the best for their disabled children but different views about the purpose of the special school affected their involvement in the education of their disabled children. Furthermore, the meaning of disability influenced father involvement in the education of disabled children. It was concluded that father involvement in the education of disabled children in this African setting was complex and presented itself in ways that were different from what formal western education expected. This study provides critical new knowledge on how father involvement in the formal education of disabled children is constructed within the context of a specific school in an African setting. The new knowledge not only adds to the current limited evidence in the literature on father involvement, but also might assist education stakeholders like ministries of education and development workers in advancing best practice regarding implementation of family support structures for disabled children's education in Africa.